Potential of Heavy Metal Pollution (Cd) in the Kapuas Kecil River - Rizki Purnaini; Ochih Saziati (Universitas Diponegoro, 2023)
The Kapuas Kecil River is a river that becomes the lifeblood of the people of Pontianak in supporting their lives. It is raw water source for Municipal Waterworks, industry, fisheries, agriculture, animal husbandry, tourism, and transportation. The variety of activities carried out on the banks of the Kapuas Kecil River contributed to the occurrence of pollution by heavy metals such as Cd. Currently, the Kapuas Kecil River flow is already crowded with industrial shipbuilding activities, which are one of the contributors to Cd metal pollution in the waters. This study aims to identify the source of Cd pollutants and determine the concentration of Cd in the Kapuas Kecil River. Sampling was carried out in October at four sampling points at low tide, then compared with the allowable Cd concentration according to PP 22/2021 which is 0.01 mg/L, and the status of water quality was determined by the pollutant index method. Based on the results of the study, the Cd concentration was still below the quality standard with a value of >0.001 mg/L, and the water quality status met the quality standard.